Community stigma on the health care providers during COVID-19 Pandemic - Yanto, Arief; Faroby, Muhammad Athfal; Hartiti, Tri; Samiasih, Amin (South East Asia Nursing Research, 2021)
Stigma can be an obstacle in efforts to prevent, treat and treat COVID- 19 patients. Negative stigma can cause psychological problems for health workers during the COVID-19 pandemic. Stigma is often associated with health problems including COVID-19 which is caused by fear and lack of knowledge. This study aims to determine the image of the community's stigma against health workers during the COVID-19 pandemic. This study used a quantitative descriptive research design with a survey approach using a questionnaire filled out via google form. Sampling was done through convenience sampling. The sample of this study was 138 respondents who met the inclusion criteria. Most of the respondents did not give stigma labelling 82.6%, did not give stigma stereotype 81.9%, did not give stigma separation 89.9% and did not give stigma discrimination 77.5% to health workers. The results showed that the community did not give stigma of labelling, stereotype, separation and discrimination to health workers during the COVID-19 pandemic. It is hoped that this research can be used as input to prevent the emergence of a negative stigma against health workers during a pandemic.